Push–pull second harmonic generation chromophores bearing pyrrole and thiazole heterocycles functionalized with several acceptor moieties: Syntheses and characterization - Castro, Maria Cidália Rodrigues (2016)
A new series of pushepull nonlinear optical (NLO) chromophores 2 and 3 were synthesized in order to study the variations produced in the optical properties of the compounds by linking different electron accepting moieties to the pyrrolyl-thiazole system at position 5 of the electron deficient thiazole heterocycle. The final donore-acceptor systems 3aec were synthesized by a modification of the PaaleKnorr synthesis (the Clauson-Kaas reaction) followed by Knoevenagel reaction of the precursor aldehydes 2aec with active methylene molecules. Hyper-Rayleigh scattering in dioxane solutions using a fundamental wavelength of 1064 nm was employed to evaluate their second-order nonlinear optical properties. An indanone dicyanovinyl derivative 3c exhibited the largest first hyperpolarizability (beta = 970x10 -30 esu, using the T convention) as well the highest value of decomposition, Td = 300 C thus indicating its potential application as a second harmonic generation (SHG) chromophore.